Sex difference in alcohol withdrawal syndrome: a scoping review of clinical studies - Unlu, Hayrunnisa; Macaron, Marie Michele; Ayraler Taner, Hande; Kaba, Duygu; Akin Sari, Burcu; Schneekloth, Terry D.; Leggio, Lorenzo; Abulseoud, Osama A. (Frontiers in Psychiatry, 2023)
We conducted a review of all studies comparing clinical aspects of alcohol withdrawal syndrome (AWS) between men and women.Methods: Five databases (PubMed, Cochrane, EMBASE, Scopus and Clinical Trials) were searched for clinical studies using the keywords "alcohol withdrawal syndrome" or "delirium tremens" limited to "sex" or "gender" or "sex difference" or "gender difference." The search was conducted on May 19, 2023. Two reviewers selected studies including both male and female patients with AWS, and they compared males and females in type of AWS symptoms, clinical course, complications, and treatment outcome.Results: Thirty-five observational studies were included with a total of 318,730 participants of which 75,346 had AWS. In nineteen of the studies, the number of patients presenting with or developing AWS was separated by sex, resulting in a total of 8,142 (13%) female patients and a total of 56,664 (87%) male patients. Despite inconsistent results, males were more likely than females to develop complicated AWS [delirium tremens (DT) and AW seizures, collective DT in Males vs females: 1,792 (85.4%) vs. 307 (14.6%), and collective seizures in males vs females: 294 (78%) vs 82 (22%)]. The rates of ICU admissions and hospital length of stay did not show sex differences. Although variable across studies, compared to females, males received benzodiazepine treatment at higher frequency and dose. One study reported that the time from first hospitalization for AWS to death was approximately 1.5 years shorter for males and males had higher mortality rate [19.5% (197/1,016)] compared to females [16% (26/163)].Despite the significant heterogeneity of the studies selected and the lack of a focus on investigating potential sex differences, this review of clinical studies on AWS suggests that men and